ANALISIS FAKTOR YANG MEMPENGARUHI PENGELOLAAN KEUANGAN KAMPUNG DI KABUPATEN JAYAPURA - Pangayow, Bill J. C.; Andriati, Hastutie Noor (Fakultas Ekonomi, Universitas Cenderawasih, 2019)
The village independence is an essential idea for the village community where they are located. Inaccordance to support this goal, the central, provincial and district/city governments provide fundsto villages that must be managed properly. Village financial management apparatuses endeavor inplanning, implementing, administering, and financial reporting in accordance with applicableregulations with supervision from the Village Consultative Body. This study aims to identifyindicators and determinants in village financial management and examine its effect on the villageindependence variable. This research will be carried out in villages of Yobeh, Ifaar Besar, Sereh,and Yahim, in Sentani District in Jayapura Regency. The analysis tool that will be used is FactorAnalysis to find key indicators and variables in financial management. The results showed thatreporting variables became the key in financial management, followed by financial accountability,planning, and implementation. This shows that respondents felt the reporting was very importantand needed to be considered in financial management.